Social Reconstructions Through The Role of Islamic Boarding Schools in Building Cross-Cultural Solidarity in Border Areas - Rokman, Rizqi Fatkhu; Erwin Mahrus; Sukino (Institut Studi Islam Muhammadiyah Pacitan, 2026)
This research aims to uncover the role of the Miftahul Hidayah Islamic Boarding School in building cross-cultural solidarity in border areas. The research method used is qualitative with a case study approach, through in-depth interviews, observations, and documentation. The results of the study show that pesantren not only functions as an institution of religious teaching, but also as a strategic center for social reconstruction that encourages the creation of intercultural harmony. Islamic boarding schools create learning spaces that are responsive to social dynamics, develop a curriculum based on the values of fairness and openness, and involve students in various social, cultural, and religious activities with the community. The leadership of kiai and teachers plays an important role in internalizing the values of tolerance, peace, and inclusivity that make students agents of peace and social stability. These findings also identify the challenges and opportunities faced by Islamic boarding schools, especially in establishing cooperation across religions, customs, and social institutions. This research confirms that Islamic values can be a solid foundation for the formation of cross-cultural solidarity while strengthening social cohesion in border areas.